Love-Based Curriculum: Integrating Islam, Humanism, and Local Wisdom in Madrasas - Abdulnasir Dhaw Alsayd; Imam Rusdi; Amin Muhtar; Nur Setyaningrum (Tuah Foundation, 2025)
This article develops an integrative conceptual model of a Love-Based Curriculum for madrasas, founded on Islamic values, humanistic principles, and Indonesian local wisdom. Using a literature study with philosophical-analytical analysis, the research maps the concept of love from three perspectives: the transcendental-moral (Islamic), psychological-interpersonal (humanistic), and socio-cultural (local wisdom). These perspectives are synthesized and integrated into four curriculum components: objectives, content, learning strategies, and evaluation. The results indicate that this synthesis yields a curriculum framework that is both theoretically robust and contextually applicable in madrasa settings. Additionally, the study proposes a love-based character evaluation rubric to assess students' affective development. The model's theoretical implications include redefining the teacher's role as a character facilitator, enhancing value-based supervision systems, and informing more humanistic Islamic education policies. The article concludes by recommending empirical testing of the model through practice-based research in madrasas.